Endoscopic Ultrasound Assessment of Solid Pseudopapillary Neoplasm of the Pancreas: Case Series in Latin American Population - Luis, Sabbagh; Gabriela, Rodríguez; Sandra, Huertas; Andrea, Rodríguez; Diego, Aponte; Daniela, Sabbagh (Current Surgical Endoscopy, 2025)
IntroductionSolid pseudopapillary tumors of the pancreas (SPN) are uncommon lesions. Endoscopic ultrasound is considered the standard examination because of its capability to acquire a suitable core tissue sample. This study details the experience of eleven cases within a Latin American population diagnosed with SPNs through the endoscopic ultrasound-guided fine needle biopsy (EUS-FNB) approach.MethodsRetrospective reviews of records from a 6-year period, from January 2018 to December 2023, were performed at Clínica Reina Sofía in Bogotá, Colombia. We included eleven patients with surgically proven solid pseudopapillary tumors who had undergone preoperative EUS−FNB. The clinical history, EUS findings, biopsies, and immunohistochemical profile were reviewed.Results and DiscussionIn this study of eleven SPN patients (median age: 31.9 years, 90.1% female, all Hispanic), abdominal pain (63.6%) was the predominant symptom. The indication for EUS was predominantly a pancreas-dependent mass (90.1%). Tumors were located more frequently on the pancreatic neck, with regular morphology, well-defined borders, and predominantly hypoechoic and heterogeneous appearances on EUS. The average tumor diameter was 4.3 cm [range 1.2- 10 cm]. Most tumors were solid (63.6%), and elastography revealed a mixed pattern. EUS-Doppler indicated hypovascularity in all cases. Vascular compression occurred in three patients. No lymph nodes were observed. There were no complications related to the procedure. The histopathological analysis using EUS-FNB yielded consistent results with post-surgical biopsies.ConclusionIn the context of diagnostic evaluation for SPNs, EUS-FNB emerges as a pivotal procedure. In this descriptive study, EUS-FNB showed a remarkable preoperative diagnostic yield of 100% compared to post-surgical histopathology for solid pseudopapillary tumors.
Keywords: solid pseudopapillary neoplasm